The complete mitochondrial genome of Colasposoma dauricum auripenne (Motschlsky, 1860) (Coleoptera: Chrysomelidae: Eumolpinae) - Xiaohui Li; Tiantian Ban; Yun Li; Chao Ma (Mitochondrial DNA. Part B. Resources, 2022)
The sweet potato leaf beetle Colasposoma dauricum auripenne (Motschlsky, 1860) (Coleoptera: Chrysomelidae: Eumolpinae) is one of the main pests in sweet potato. In this study, the complete mitochondrial genome of Colasposoma dauricum auripenne (Motschlsky, 1860) (Coleoptera: Chrysomelidae: Eumolpinae) has been sequenced. The mitogenome length is 15,614 bp (GenBank: MW528208), which includes 13 typical insect protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), and 22 transfer RNA genes (tRNAs), and it contains 78.6% A + T and 21.4% G + C. All PCGs start with ATD (ATT, ATA, ATG) codon and stop with termination codon TAA, TAG and single T. The phylogenetic tree showed that Colasposoma had been cluster together, and form a sister group relationship with Pseudocolaspis. The complete mitogenome of C. dauricum auripenne would help understand Chrysomelidae evolution.